Grassypeptolides as Natural Inhibitors of Dipeptidyl Peptidase 8 and T‐Cell Activation. Issue 6 (3rd March 2014) - Kwan, Jason C.; Liu, Yanxia; Ratnayake, Ranjala; Hatano, Ryo; Kuribara, Akiko; Morimoto, Chiko; Ohnuma, Kei; Paul, Valerie J.; Ye, Tao; Luesch, Hendrik
Abstract Natural products made by marine cyanobacteria are often highly modified peptides and depsipeptides that have the potential to act as inhibitors for proteases. In the interests of finding new protease inhibition activity and selectivity, grassypeptolide A (1) was screened against a panel of proteases and found to inhibit DPP8 selectively over DPP4. Grassypeptolides were also found to inhibit IL‐2 production and proliferation in activated T‐cells, consistent with a putative role of DPP8 in the immune system. These effects were also observed in Jurkat cells, and DPP activity in Jurkat cell cytosol was shown to be inhibited by grassypeptolides. In silico docking suggests two possible binding modes of grassypeptolides—at the active site of DPP8 and at one of the entrances to the internal cavity. Collectively these results suggest that grassypeptolides might be useful tool compounds in the study of DPP8 function.